Key Economic Parameters for an Optimal Pharmacy Network in a Regulated Environment - Franjo MLINARIC; Zan Jan OPLOTNIK; Bostjan BREZOVNIK (Transylvanian Review of Administrative Sciences, 2016)
Pharmacies are an integral part of the modern healthcare system which strives for a holistic and effi cient care. General practitioners and pharmacists are held in high esteem among local communities as they are the fi rst point of contact when people have health issues. However, a strong demand for health services in developed countries and its present fi nancing schemes undermined the sustainability of the whole health system (8.9% of GDP in 2013 and growing). According to WHO and EU recommendations, the whole healthcare system shall accept a holistic approach and focus on education, prevention and proper medicine consume. Part of this strategy is a seamless care concept, where medical doctors and pharmacists build a team around the well-being of a patient. Financing scheme incentives and KPI’s (key performance indicators) will be focused on keeping people healthy, instead of paying for procedures. The future healthcare ecosystem obliges pharmacists to optimize network coverage and to extend health services. Nevertheless, their growth strategy needs to be gradual, considering the present level of network coverage, the low pace of private and public expenditures for medicine and services, and the fact that a new fi nancing model for pharmacies is still unknown. Thus, we expect the development of pharmacy network in regulated environment to be fi nanced predominantly from retained earnings in publicly owned pharmacies and by awarding pharmacy concessions.